Know My Language, Know My Music, Know My Culture: adapting a music education unit in regional Australia to meet the individual needs of pre-service teachers (Orfeu, 2018)
Music is an integral part of society. How it is taught and represented in educational institutions reflects the educational values. Moreover, it is part of a nation’s cultural fabric. The paper will discuss the issues pertaining to music education courses in Australia and postulate why an individualised curriculum at the pre-service teacher stage is necessary. From this, an existing unit has been adapted to meet the needs of pre-service teachers in regional and remote areas of Australia. A mix methods approach of Critical Discourse Analysis and Participation Action Approach has been used. This has been necessary to identify and understand the issues of identity, access and inclusiveness. Through these changes, the unit was transformed to better align with the individual needs of pre-service teachers, the changing environment of schools and the Year 11 and 12 music curriculum.
Keywords: Australian Curriculum; equity; Indigenous music; music education; online learning